The perceptions of integrity of three public agency in Kuala Terengganu / Iskandar Hasan Tan Abdullah, Asri Salleh and Jazimin Zakaria - Abdullah, Iskandar Hasan Tan; Salleh, Asri; Zakaria, Jazimin (2010)
Malaysia in its effort to become a fully developed nation by 2020 has undertaken a monumental task in instilling noble values into its society including its civil sector. The integrity of the civil servants needs to be greatly improved in order to turn this vision into a reality. This project attempted to examine the level of awareness, knowledge and understanding on noble values particularly integrity among selected civil servants in selected State Government agencies in Terengganu, Malaysia. The respondents were selected based on a purposive sampling technique. The research used a quantitative approach where self-administered structured questions were distributed. Descriptive and inference analysis were carried out to meet the research objectives outlined. The research findings showed that there were civil servants groups who were unclear and uncertain about the meaning of integrity in public sector. Those with shorter length of services were less knowledgeable on the rule and procedure which led to them being unsure about integrity. Length of service was found to be inversely related to the perception on the knowledge of integrity, corruption and quality of service delivery. Since this research was confined only on civil servants of selected State agencies in Terengganu, future studies may use this research as a point of reference for larger sample size study on the same topic.